Identification of an AFLP marker linked with yellow rust resistance in wheat (Triticum aestivum L.) - ALTINKUT UNCUOĞLU, AHU; AYDİN, YILDIZ (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2014)
An important application of molecular markers in plant systems involves improvement in the efficiency of conventional plant breeding by carrying out indirect selection through molecular markers linked to the traits of interest. AFLP analysis was used to identify molecular markers associated with yellow rust resistance in wheat (Triticum aestivum L.) in this study. DNA isolated from the selected yellow rust tolerant and susceptible F 2 individuals derived from a cross between Izgi2001 (resistant) and ES14 (susceptible) at seedling and adult stage was used for bulked segregant analysis combined with AFLP. From the screening of 34 PstI/MseI AFLP primer combinations, the AFLP marker P-GAC/M-ACG (133 bp) was identified and presented in the resistant parent and resistant F 2 individuals but not in the susceptible ones. Future research will obtain more adjacent sequences associated with the polymorphic M-ACG/P-GAC (133bp) marker by the PCR walking method to design SCAR markers for wheat breeding programs.
Keywords: AFLP; bread wheat; disease resistance; SCAR; yellow rust; FRAGMENT LENGTH POLYMORPHISM; BULKED SEGREGANT ANALYSIS; GENETIC DIVERSITY; STRIPE RUST; MICROSATELLITE MARKERS; HEAT TOLERANCE; SCAR MARKER; CONVERSION; RICE; QTL